A Novel Subcutaneous Pancreatic Islet Transplantation Method Using the New Device of Recombinant Peptide Containing Human Type I Collagen Material with RGD motif (Arg-Gly-Asp). (July 2018) - Uematsu, Satomi; Inagaki, Akiko; Nakamura, Yasuhiro; Imura, Takehiro; Igarashi, yasuhiro; Fathi, Ibrahim; Miyagi, Shigehito; Kamei, Takashi; Unno, Michiaki; Satomi, Susumu; Goto, Masafumi
Abstract : Introduction: Subcutaneous islet transplantation has many advantages including its minimal invasiveness, thus it is considered to be one of the ideal transplant sites for pancreatic islets, compared with the intraportal islet transplantation. However, it is well known that subcutaneous site has poor vascularization. Although the effectiveness of basic fibroblast growth factor (bFGF) on this issue was previously reported, it often causes bleeding, making it difficult to use for diabetic patients. In order to overcome these drawbacks, we herein investigated a new material device, Recombinant Peptide(RCP) containing human type I collagen together with RGD motif (Arg-Gly-Asp), as alternative for bFGF pretreatment. Materials and Methods: The RCP (10 days before islet transplantation:RCP 10D group, 4 weeks before islet transplantation:RCP 4W group) or vehicles containing 10 ug of bFGF togetehr with 10 U of heparin (bFGF 10 group) were implanted into the subcutaneous space of streptozotocin-induced diabetic C57BL/6 mice, and marginal amount of syngeneic islets(660 IEQs) were transplanted into the prevascularized space after removal of the devices. The portal vein transplantation group (Ipo group), the group with only vehicle not containing bFGF or heparin (bFGF 0 group), the Sham group, and the group without any prevascularization procedures (None group) were set up and examined as control groups. Results and Discussion: The cure rates of the Ipo and bFGF 10 group were significantly higher than those of the Sham and None groups (P <0.01, 0.05). In the RCP groups, the efficiency in the RCP 4W group was better than that in the bFGF 10 group, furthermore, comparable to that in the Ipo group (100% vs. 75% vs. 87.5%). In contrast, the cure rate of the RCP 10D group was significantly lower than that of the RCP 4W and Ipo groups (P <0.01, 0.05). Unlike bFGF, no bleeding and effusion were observed in the RCP groups. The area under the curve of the RCP 4W group in the glucose tolerance test was even better than that of the Ipo group (23, 866.5±3372 vs. 31, 581.7±3310 min*mg/d), and it was also significantly lower than that of the None, Sham, and RCP 10D groups (P<0.01, resectively). The number of vWF-positive vessels in the bFGF 10 group was significantly higher than that in the None and bFGF 0 groups (P<0.01, resectively), whereas the efficiency of neovascularization in the RCP groups appeared to be lower than the bFGF 10 group, suggesting that the other factors including the compensation of the lost extracellular matrices of the isolated islets, as well as neovascularization, might be crucial for successful subcutaneous islet transplantation. Conclusions: The present study showed that subcutaneous islet transplantation could be performed as efficiently as intraportal islet transplantation with the establishment of an optimized protocol by introducing RCP device. In this regard, the use of materials that induce efficient prevascularization would be a novel therapeutic approach for improving subcutaneous islet engraftment. Megumi Goto. Maya Imura .